Synergistic Association of House Endotoxin Exposure and Ambient Air Pollution with Asthma Outcomes - Mendy, Angelico (Am J Respir Crit Care Med, 2019)
Rationale: House endotoxin and ambient air pollution are risk factors for asthma; however, the effects of their coexposure on asthma are not well characterized. Objectives: To examine potential synergistic associations of coexposure to house dust endotoxin and ambient air pollutants with asthma outcomes. Methods: We analyzed data of 6,488 participants in the National Health and Nutrition Examination Survey 2005–2006. Dust from bedding and bedroom floor was analyzed for endotoxin content. The Community Multiscale Air Quality Modeling System (CMAQ) and Downscaler Model data were used to determine annual average particulate matter ≤2.5 μm in aerodynamic diameter (PM(2.5)), ozone (O(3)), and nitrogen dioxide (NO(2)) exposures at participants’ residential locations. The associations of the coexposures with asthma outcomes were assessed and tested for synergistic interaction. Measurements and Main Results: In adjusted analysis, PM(2.5) (CMAQ) (odds ratio [OR], 1.12; 95% confidence interval [CI], 1.07–1.18), O(3) (Downscaler Model) (OR, 1.07; 95% CI, 1.02–1.13), and log(10) NO(2) (CMAQ) (OR, 3.15; 95% CI, 1.33–7.45) were positively associated with emergency room visits for asthma in the past 12 months. Coexposure to elevated concentrations of house dust endotoxin and PM(2.5) (CMAQ) was synergistically associated with the outcome, increasing the odds by fivefold (OR, 5.01; 95% CI, 2.54–9.87). A synergistic association was also found for coexposure to higher concentrations of endotoxin and NO(2) in children (OR, 3.45; 95% CI, 1.65–7.18). Conclusions: Coexposure to elevated concentrations of residential endotoxin and ambient PM(2.5) in all participants and NO(2) in children is synergistically associated with increased emergency room visits for asthma. Therefore, decreasing exposure to both endotoxin and air pollution may help reduce asthma morbidity.